Spectacle and "Shedifice": Wellington's Ambiguous Role in the Reception of the Duke of Edinburgh - McDonald, Chris (Architectural History Aotearoa, 2010)
New Zealand's first royal tour occurred in 1869 just four years after Wellington became the seat of the colonial government. The Duke of Edinburgh's short visit left no permanent physical impression on the new capital other than the four trees he planted in the garden of Government House (now Parliament Grounds). Nevertheless, the Duke's reception was an overtly Imperial occasion which highlighted the colonial character of Wellington's incipient ceremonial spaces. In developing this argument, the paper shows how the Australasian colonies adopted a highly standardised format for their reception of royal visitors. Indeed, it will be shown that the first royal visits to Australia and New Zealand were the region's first pan-colonial event. At the same time, the Duke's reception in New Zealand, revealed much about the young colony's still-fluid political geography. In particular, the tour drew attention to the weak and unstable nature of many public institutions. Amid intense inter-provincial rivalry of the 1860s, the royal visit also highlighted the ambiguous relationship between New Zealand's new capital and the colony's other centres of European population. Wellington's response to the royal visit differed little from those of Christchurch and Dunedin, indeed the capital was upstaged by the younger and wealthier settlements in the South Island. Meanwhile, Auckland retained many of the attributes of a colonial capital. One British commentator went so far as to suggest that Wellington was not a "real" capital, in the manner of Melbourne or Sydney. The paper examines this proposition, and draws conclusions about Wellington's true status in the colony at the close of the decade.